EVALUATION OF HOUSEWIVES' DOMESTIC VIOLENCE EXPERIENCES WITHIN THE FRAMEWORK OF EMPOWERMENT APPROACH (Third Sector Social Economic Review, 2024)
Domestic violence is a phenomenon that has become a problem not only in our society but all over the world. Intimate partner violence and domestic violence are concepts that have similar negativities and are often used interchangeably. In this study, in which housewives' experiences of violence by their husbands were investigated, the concept of violence was used instead of both intimate partner violence and domestic violence in order not to make the writing boring in the literature. The aim of this study is to investigate the experiences of housewives of being subjected to physical, psychological, sexual and economic violence from their husbands, as well as the invisibility of the effort and energy they spend at home, and to make suggestions within the framework of the empowerment approach regarding the welfare services that women who are victims of violence need. Phenomenology design, one of the qualitative research designs, was used in the study. Using criterion sampling, which is one of the purposeful sampling methods of qualitative research, the study group was selected from the housewives residing in Kağıthane district of Istanbul province who were married and had experiences of domestic violence by their spouses. A semi-structured interview form was used to collect data from the participant housewives. Descriptive analysis was used to analyze the data.
Keywords: Domestic violence; housewife; empowerment approach; intimate partner violence